Adat Jawa Dalam Asuhan Kehamilan Perspektif Hukum Islam - Rofika Dwi Permata Sari; Nur Wakhidah; Ergina Faralita (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2024)
Javanese traditional traditions in pregnancy have strong cultural values, such as the mitoni event (seven months of pregnancy) and other rituals. This tradition is often seen as a form of respect for the ancestors as well as hope for the safety of the mother and baby. This research aims to analyze jaa pregnancy customs from an Islamic perspective. Using a descriptive qualitative research method and analysis of Islamic literature and culture, it was found that several traditions have positive values, such as strengthening relationships and providing psychological support to pregnant women. However, practices that conflict with monotheism, such as belief in certain objects or rituals as determinants of salvation, need to be straightened out. In the maslahah concept, this tradition can be preserved provided that it is adapted to suit Islamic values, thereby providing benefits without violating religious principles. This research emphasizes the importance of synergy between custom and religion to create Islamic cultural harmony. The results of research on Javanese customs in pregnancy from an Islamic perspective with a maslahah (benefit) approach usually highlight how local traditions are in harmony or not with the principles of Islamic law.